Herbicidal weed control in drill sown spring wheat under Bangladesh condition - Ahmed, Sharif; Alam, Md Jahangir; Awan, Tahir Hussain; Islam, A K M Mominul (Fundamental and Applied Agriculture, 2019)
Weeds are considered as one of the major factors responsible for current low wheat yield in Bangladesh. Although chemical weed control is well estab- lished in many wheat growing countries, in Bangladesh, the herbicides are typically not used by farmers to manage weeds in wheat. Hence, to evaluate the efficacy of pre- and post-emergence herbicides in mechanized drilled sown wheat, a two-year field study was conducted in southwest Bangladesh. The study evaluated the performance of four pre-emergence herbicides (oxadiargyl 80 g, pendimethalin 850 g, pyrazosulfuron 15 g, and mefenacet + bensulfuran methyl 550 g active ingredient ha−1) applied at 2 days after sow- ing (DAS) and four post-emergence herbicides (2,4-D 1400 g, ethoxysulfuron 18 g, penoxsulam 22.5 g, and fenoxaprop 56 g active ingredient ha−1) applied at 20 DAS, on weed control efficacy. A season long weed-free and a season long weedy plots were also maintained to compare the results. The weed con- trol option using a single pre- or post-emergence herbicide was not adequate to control weed effectively when weed infestation was relatively higher. The best yield provided by pre-emergence (pendimethalin and oxadiargyl) and post-emergence (2,4-D and ethoxysulfuron) herbicide treatments were respec- tively 13-15% and 12-17% lower than the yield (4.1-4.2 t ha−1) of weed-free treatment. Post-emergence herbicides fenoxaprop was the best in controlling weeds; however, due to phytotoxic effects on wheat plants, the plots applied with fenoxaprop produced very low yield (2.6-2.8 t ha−1). Similarly, even after good weed control by the post-emergence application of penoxsulam, phytotoxicity on wheat resulting in low yield. The study suggested that the best weed control option for wheat is to use a pre-emergence (pendimethalin or oxadiargyl) followed by (fb) a post-emergence (2,4-D or ethoxysulfuron) herbicides depending upon weed species which would benefit the farmers by providing high weed control efficacy at lower cost compared to manual weeding.